Nerve regeneration techniques respecting the special characteristics of the inferior alveolar nerve. Issue 9 (September 2016) - Hergt, Ansgar C.; Beck-Broichsitter, Benedicta E.; Raethjen, Jan; Käser, Nathalie; Hülsmann, Michael; Wiltfang, Jörg; Heine, Jörg; Becker, Stephan T.
Abstract: Purpose: The aim of this study was to examine the in situ regeneration of the inferior alveolar nerve (IAN) in its bony channel, using autologous tissue in combination with a recombinant human nerve growth factor (rhNGF). Materials and methods: A total of 20 New Zealand rabbits were randomly divided into five groups. Following dissection of the IAN, the animals underwent reconstruction either with muscle tissue (groups 1 and 2) or with fat tissue (groups 3 and 4). In group 5 (control), the dissected nerve was resected and reconstructed by placement of the reversed autologous segment. After 2 and 4 weeks, 1 mL rhNGF was locally injected in groups 1 and 3. Nerve function was monitored by measuring the jaw-opening reflex using electromyography for a period of 24 weeks. Results: Regeneration of the nerve was achieved in all groups, but preoperative threshold values were not achieved. Comparing the experimental groups to the control, there was a significant difference in favor of the autologous nerve reconstruction. Differences between the experimental groups remained statistically not significant. Conclusion: Regeneration of the IAN with autologous tissue is possible, but without achieving preoperative thresholds. Additional injection of a growth factor seems to improve the speed of regeneration for fat and muscle grafts.